Biogranulation technologies for wastewater treatment (Elsevier, 2006)
The book covers almost all aspects of formation and use of microbial granules in wastewater treatment. The data on aerobic microbial granulation are related mostly to laboratory systems due to few pilot systems in the world using aerobic microbial granules. This book will help researchers and engineers develop these new biotechnologies of wastewater treatment based on aerobic granulation